Tailoring the electrolyte and cathode properties for optimizing the performance of symmetrical solid oxide fuel cells fabricated by one-step co-sintering method - Chuanming Li; Qingshuai Zhang; Wei Liu; Xiangxin Tian; Rongkun Zheng; Jingquan Liu (Journal of Asian Ceramic Societies, 2022)
Symmetrical solid oxide fuel cells (S-SOFCs) are prepared via a facile one-step co-sintering method with highly reactive Sm0.2Ce0.8O1.9 (SDC) electrolyte and Sr2Fe1.5Mo0.5O6-δ (SFM) electrodes. The phase compositions and microstructures are studied by XRD, TEM, and FESEM techniques, and the electrolyte-supported single cells with gas-tight SDC electrolyte and porous SFM-SDC electrode are prepared after one-step co-sintering at 1100 °C or higher temperatures for 4 h. In particular, the AC impedance spectra reveal that the SDC electrolyte sintered at 1200 °C exhibits the highest oxide ionic conductivity of ~35 mS/cm at 700 °C, while the electrode polarization resistance achieves the lowest value of 0.32 Ω·cm2 at 700 °C in air for the sample co-sintered at 1100 °C. Accordingly, the output measurements are carried out on the single cells co-sintered at 1100 °C and 1200 °C. It is found that the single cell co-sintered at 1200 °C possesses the highest peak power density of 216 mW/cm2 at 700 °C, demonstrating the potential application of the one-step co-sintering method in low-cost manufacturing of S-SOFCs.